Foreign Direct Investment: A Comparative Analysis between Iraq and the UAE - Ghazwan Abdulhadi Alabdalrahman; Haniff Ahamat; Nabeel Mahdi Althabhawi (Sriwijaya Law Review, 2023)
Foreign direct investment (FDI) refers to an investment into a company or organisation through long-term or overseas expansion acquisition with the hope of forming a long-term relationship. It is a viable business tool utilised in businesses across the globe. However, in Iraq, despite the investment laws and other regulations to boost foreign direct investment, investors still need to be convinced about investing in Iraq due to several factors that might affect their investments. Many countries and some Arab countries have advanced in their FDIs, leaving Iraq behind, one of which is the UAE. Therefore, this research aims to analyse Iraqi's FDI vis-à-vis what is obtainable in the UAE to proffer effective and appropriate recommendations to be implemented to boost the Iraqi FDI for better future investments. To achieve this, the study utilised a theoretical method of review of existing literature and relevant legislations in the two jurisdictions, as well as a  comparative analysis to analyse the key areas hindering the effectiveness of the Iraqi FDI compared to what is obtainable in the UAE. It was discovered that besides the dispute resolution mechanism, corruption, poor infrastructure, unskilled labour, political instability and the financial sector, the legal framework is inadequate, incomprehensive, and discouraging to foreign investors. However, these hindrances are not prevalent in the UAE. Hence, the suggestion for Iraq to boost its political stability, social security, improve its business climate and transfer knowledge and practices from the UAE to achieve a robust FDI in Iraq in fulfilment of SDG 17.